Perkembangan Anak Ditinjau dari Teori Mature Religion - Windisyah Putra (FITK UIN Walisongo, 2013)
Physical development is not necessarily equivalent to spiritual development. Normally, a person who has reached maturity level will have spiritual maturity pattern such as thought maturity, personal maturity, and emotional maturity. Yet, the balance between physical maturity and spiritual maturity sometimes does not run in parallel. One may have grown physically but not spiritually. Re-ligious values need to be established in children since early ages. The religious values mean any deeds relating humans and God or among human beings rela-tionship. Physical development is measured based on chronological age, peak of human physical development which is called maturity. On the other hand, spir-itual development is measured based on level of ability and certain ability level achieved by spiritual development which is called maturity.AbstrakKedewasaan jasmani belum tentu berkembang setara dengan perkembangan ro-hani. Umumnya orang dewasa memiliki pola kematangan rohani tetapi dalam beberapa kasus keduanya tidak berkembang secara seimbang. Secara fisik, seseorang mungkin sudah dewasa tetapi secara rohani ia ternyata belum matang, termasuk kematangan keberagamaannya. Nilai-nilai keagamaan perlu ditanamkan kepada anak sejak usia dini. Perkembangan jasmani diukur berdasarkan umur kronologis. Puncak perkembangan jasmani yang dicapai manusia disebut dengan kedewasaan. Perkembangan rohani diukur berdasarkan tingkat kemampuan; pencapaian tingkat abilitas tertentu bagi perkembangan rohani disebut dengan istilah kematangan.